Sosialisasi Penggunaan Gadget yang Bijak pada Anak Sekolah Dasar di Rt 01/Rw 02 Kelurahan Simpang Haru, Kecamatan Padang Timur Kota Padang Sebagai Upaya Meningkatkan Ketahanan Nasional - Elwidarifa Marwenny; Indrayeni Indrayeni; Defika Yufiandra; Naya Klaresa; Abelto Abelto; Riska Aulia; Balqis Darratul Hikmah; Haril Aditya Nasfi; Intan Elsa Tri Dermawan; Oktria Oktria; Khairunisa Khairunisa; Afifah Saidah; Agung Hartanto; Bagas Al'kautsar (CV. ITTC INDONESIA, 2026)
Rapidly increasing access to technology among elementary school children presents distinct challenges, ranging from the risk of digital addiction and exposure to negative content to a decline in social interaction—factors that could potentially erode character values ​​and national resilience. This community service initiative aims to enhance elementary-aged children's understanding and awareness regarding the wise, safe, and responsible use of digital devices. The outreach activity was conducted in the RT 01/RW 02 neighborhood of Simpang Haru Urban Village, East Padang District, Padang City. An educational and participatory approach was employed, featuring interactive talks using accessible language, two-way discussions, educational games (ice-breakers), and the reinforcement of digital ethics grounded in local Minangkabau wisdom. Participant understanding was evaluated through oral quizzes and interactive Q&A sessions at the conclusion of the event. The activity met with great enthusiasm from the participants. Most children were able to understand and articulate the benefits of devices for learning, the negative impacts of excessive use, the importance of healthy usage limits, and appropriate actions to take when encountering negative online content. This initiative successfully fostered early digital literacy, serving as a foundation for character building among the younger generation to support national resilience in the digital era.